A Study on the Effect of Operating Parameters on the Efficiency of a Mercury Removal Unit From Natural Gas - Mohsen, Ahmed; Farouq, Rania; Farag, Hassan A.; Salem, Mostapha (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study, an industrial fixed-bed for mercury adsorption from natural gas, was evaluated by mathematical models. Equilibrium isotherms, kinetics equations, and adsorption models were applied to available data to evaluate sorbent characteristics, and then study bed`s performance under different case studies. Models solutions are evaluated by linear-regression and coefficient of determination.
Keywords: natural gas; mercury removal; adsorption; chemisorption; mathematical models; gaz ziemny; usuwanie rtęci; adsorbcja; chemisorpcja; modele matematyczne